Down the Not So Straight and Narrow: A Rare Case of Primary Urethral Squamous Cell Carcinomas in a Young Patient - Kevin Yinkit Zhuo; Aditya Sharma; Chloe Wilcox; Cameron Parkin; Nicola Jeffery; Amanda Chung (Société Internationale d’Urologie Journal)
None.